Myeloid-derived suppressor cells in influenza virus-induced asthma exacerbation - van Geffen, Chiel; Lange, Tim; Kolahian, Saeed (Frontiers in Immunology, 2024)
Myeloid-derived suppressor cells (MDSCs) are a phenotypically heterogenous group of cells that potently suppress the immune response. A growing body of evidence supports the important role of MDSCs in a variety of lung diseases, such as asthma. However, the role of MDSCs in asthma exacerbation has so far not been investigated. Here, we studied the role of MDSCs in a murine model of influenza virus-induced asthma exacerbation. BALB/c mice were exposed to house dust mite (HDM) three times a week for a total of five weeks to induce a chronic asthmatic phenotype, which was exacerbated by additional exposure to the A/Hamburg/5/2009 hemagglutinin 1 neuraminidase 1 (H1N1) influenza virus. Induction of lung inflammatory features, production of T helper (Th) 1- and Th2- associated inflammatory cytokines in the lavage fluid and an increased airway hyper-responsiveness were observed, establishing the asthma exacerbation model. The number and activity of pulmonary M-MDSCs increased in exacerbated asthmatic mice compared to non-exacerbated asthmatic mice. Furthermore, depletion of MDSCs aggravated airway hyper-responsiveness in exacerbated asthmatic mice. These findings further denote the role of MDSCs in asthma and provide some of the first evidence supporting a potential important role of MDSCs in asthma exacerbation.